2020
DOI: 10.1109/access.2020.2972580
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Machining Accuracy Utilizing Varied Cooling Oil Volume for Machine Tool Spindle

Abstract: In this study, varied cooling oil volume (VOV) control was developed for the oil coolant of a machine tool. This allows adjustment of the oil circulation flow rate in terms of the machining loads and rotational speeds of the spindle to remove the generated heat effectively from the spindle. A mathematical model of the cooling oil flow rate in terms of the rotating speed and torque of the spindle for VOV method is developed. From the thermal deformation experiments with the VOV method, the thermal deformations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
(21 reference statements)
0
13
0
Order By: Relevance
“…The van Hove singularities occur where the derivative of the DOS with respect to energy E diverges, which yields a strikingly sharp peak in the DOS spectra. (38)(39)(40)(41)(42)(43) Therefore, in a perfect flat-band z4ANR, the DOS diverges at the onset of each subband, as shown in Figs. 5(a) In quantum transport devices such as DBSs, a series of discrete and fine confined levels (or states) exist in the central channel, and a continuous distribution of states exists in the left and right contacts.…”
Section: Resultsmentioning
confidence: 91%
“…The van Hove singularities occur where the derivative of the DOS with respect to energy E diverges, which yields a strikingly sharp peak in the DOS spectra. (38)(39)(40)(41)(42)(43) Therefore, in a perfect flat-band z4ANR, the DOS diverges at the onset of each subband, as shown in Figs. 5(a) In quantum transport devices such as DBSs, a series of discrete and fine confined levels (or states) exist in the central channel, and a continuous distribution of states exists in the left and right contacts.…”
Section: Resultsmentioning
confidence: 91%
“…One approach is compensation, which also includes the cooling techniques discussed in this paper. The application of special materials (e.g., [44,45]) and targeted heating (e.g., [46,47]) as well as design adaptions (e.g., [48,49]) are also assigned to compensatory measures. Another approach is the application of corrective measures.…”
Section: Influence Of Thermal Load On Manufacturing Accuracymentioning
confidence: 99%
“…The temperature of the circulating coolant is reduced in the plate heat exchanger, and the low-temperature coolant is pumped to the rotating spindle to remove the heat generated in the operational process. (12,13) In this study, the ambient temperature was treated as the reference temperature for the return coolant. The coolant temperature sensor at the inlet of the plate heat exchanger instantly responds to the inverter of the compressor to adjust the refrigerant flow rate in the refrigeration cycle in accordance with the cooling load variation of the spindle.…”
Section: Spindle Cooling Systemmentioning
confidence: 99%
“…It was found that the heat transfer coefficient was increased by increasing the surface roughness. Li et al (12,13) performed multiphysics simulation analysis on the cooling channel design of a built-in spindle. The design of experiments (DOE) method was employed to optimize the dimensions of the cooling channel, and practical machining experiments were performed to validate the thermal performance of the design.…”
Section: Introductionmentioning
confidence: 99%